Two is best? The persistence of a two-child family ideal in Europe - Tomáš Sobotka; Éva Beaujouan (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2014)
How persistent and universal has the two child family ideal been in Europe during the last three decades? We analyse responses of women of reproductive age from 168 surveys conducted in 37 countries in 1979-2012. A two-child ideal has become nearly universal among women in all parts of Europe. Countries that used to display higher ideal family size have converged over time towards a two-child model. Six out of ten women in Europe consider two children as ideal and this proportion is very similar in different regions. The mean ideal family size has become relatively closely clustered around 2.2 in most countries. Gradual shifts can be documented towards more women expressing an ideal of having one child (and, quite rarely, having no children) and a parallel decline in an ideal of three or more children. An increasing number of European countries saw their mean ideal family size falling to relatively low level around 1.95-2.15. But with an exception of one survey for eastern Germany and a few additional surveys not included in our study due to high nonresponse, none of the analysed surveys suggests a decline of mean ideal family size to levels considerably below replacement, i.e., below 1.9 children per woman. Data for countries outside Europe suggest a global spread of two-child preferences, also in many countries where the fertility transition is still in progress.
Keywords: 300; fertility ideals; ideal family size; fertility preferences; below-replacement fertility; Europe